2023
DOI: 10.1093/sleep/zsad061
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of pain pathways by experimental sleep disturbances in humans: central pain-inhibitory, cyclooxygenase, and endocannabinoid pathways

Abstract: Study Objectives There is strong evidence that sleep disturbances are an independent risk factor for the development of chronic pain conditions. The mechanisms underlying this association, however, are still not well understood. We examined the effect of experimental sleep disturbances on three pathways involved in pain initiation/resolution: (1) the central pain-inhibitory pathway, (2) the cyclooxygenase (COX) pathway, and (3) the endocannabinoid (eCB) pathway. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It was demonstrated that experimental sleep disturbances compromised central pain-inhibitory pathway predominantly in females, and activated the inflammatory cyclooxygenase pathway (by producing inflammatory prostaglandins), predominantly in males [97]. This study provides proof-of-concept that alterations in pain pathways by sleep disturbance might be sex-specific, implying different pain therapeutic targets in females and males.…”
Section: Expanding Knowledge On Mechanisms Linking Insomnia Symptoms ...mentioning
confidence: 68%
“…It was demonstrated that experimental sleep disturbances compromised central pain-inhibitory pathway predominantly in females, and activated the inflammatory cyclooxygenase pathway (by producing inflammatory prostaglandins), predominantly in males [97]. This study provides proof-of-concept that alterations in pain pathways by sleep disturbance might be sex-specific, implying different pain therapeutic targets in females and males.…”
Section: Expanding Knowledge On Mechanisms Linking Insomnia Symptoms ...mentioning
confidence: 68%
“…Sleep disorders have been found to potentially occur in the central pain inhibition pathway, Cyclooxygenase (COX) pathway, and endogenous Cannabinoid (eCB) pathway [23]. A case study reported the development of symptoms such as anxiety, irritability, lethargy, insomnia, aggression, impulsivity, and hypomania in a patient with depression and Spondylolisthesis after taking Celecoxib, a cyclooxygenase-2…”
Section: Discussionmentioning
confidence: 99%